2015
DOI: 10.5603/ep.2014.0059
|View full text |Cite
|
Sign up to set email alerts
|

Badanie metodą jednostopniowej amplifikacji kwasu nukleinowego węzłów chłonnych w raku brodawkowatym tarczycy — porównanie z badaniem histopatologicznym i badaniem PCR w czasie rzeczywistym

Abstract: First one-step nucleic acid amplification testing in papillary thyroid cancer lymph nodes -a comparison with histopathology and real-time PCRBadanie metodą jednostopniowej amplifikacji kwasu nukleinowego węzłów chłonnych w raku brodawkowatym tarczycy -porównanie z badaniem histopatologicznym i badaniem PCR w czasie rzeczywistym AbstractIntroduction: The significance of lymph node metastases and the optimal extent of lymphadenectomy remain matters of controversy in papillary thyroid cancer. This study was desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
(48 reference statements)
1
2
0
Order By: Relevance
“…The OSNA technique was evaluated in two studies on thyroid cancer patients. Their results for the detection of sentinel lymph nodes were similar to those obtained using standard histopathology or molecular techniques [ 22 , 23 ]. The aim of the study is to determine the efficacy of OSNA and SLN biopsy in the intraoperative detection of nodal involvement.…”
Section: Introductionsupporting
confidence: 65%
“…The OSNA technique was evaluated in two studies on thyroid cancer patients. Their results for the detection of sentinel lymph nodes were similar to those obtained using standard histopathology or molecular techniques [ 22 , 23 ]. The aim of the study is to determine the efficacy of OSNA and SLN biopsy in the intraoperative detection of nodal involvement.…”
Section: Introductionsupporting
confidence: 65%
“…This is therefore the first study to examine the usefulness of SLNB-OSNA in this type of tumor. In a previous collaborative study, we found a good correlation between the conventional cytological and histological data and the OSNA technique in the analysis of lymph (24). The present study analyzes the results obtained with OSNA in application to SLNB in a group of 35 patients with PTC.…”
Section: Discussionmentioning
confidence: 69%
“…54 articles did not have sufficient data for diagnostic testing. In summary, 61 articles involving 7 cancer types were included in the meta-analysis ( 9 , 10 , 13 71 ). Four cancer types, including bladder cancer, head and neck squamous cell carcinoma, ovarian cancer and pancreatic cancer, were not included for meta-analysis, due to limited literature.…”
Section: Resultsmentioning
confidence: 99%